The true inventor of some early mechanical engineering devices and mechanisms - Faris, Waleed Fekry; Elmoselhy, Salah (IIUM Press, International Islamic University Malaysia, 2017)
For centuries the inventions of automated crankshaft, camshaft, reciprocating double-action piston suction hydraulic pump with suction pipes, overshot curvaceous water turbines, andcrank-connecting rod mechanism have been credited to Leonardo da Vinci (1452 – 1519) and Lester Allan Pelton (1829 – 1908). Recently,the concepts of these proven significant inventions in fluid mechanicsand energy conversion systems have been found mentioned in themanuscripts of an inventor whose name is Abu-Aliz Al-Jazari(1136-1206). Leonardo da Vinci got these ideas from Al-Jazari’smanuscripts and did not acknowledge Al-Jazari in his relevantmanuscripts. In Lester Allan Pelton receives the credit for inventingthe over-shot curvaceous water turbine whereas the over-shotcurvaceous water turbine was described in Al-Jazari’s manuscriptwhich was made publicly available for reading many centuriesbefore the time of Lester Allan Pelton. The concepts of theseinventions which are described in Al-Jazari’s manuscripts provesthat his manuscripts were among the sources from which Leonardoda Vinci got these ideas and that Al-Jazari invented the over-shotcurvaceous water turbine many centuries before Lester Allan Peltonare presented in this paper. It has been virtually proved that the trueinventor of automated crankshaft, camshaft, reciprocating double-action piston suction hydraulic pump with suction pipes, overshot curvaceous water turbines, and crank-connecting rodmechanism is Abu-Aliz Al-Jazari.